The Role of Village Heads as Development Administrators in Enhancing Village Development Governance - Andi Anita Rahma; Muh. Darwis; Nasir Nasir (ASHA Publishing, 2026)
Village development is an integral part of national development, which emphasizes efforts to improve community welfare through planning and implementation based on local needs. In this case, the village head plays the role of a development administrator who is responsible for the effectiveness of each stage of development, from planning to supervision. The role of the village head is not only demanded in the administrative aspect but also in the management of resources in a participatory, transparent, and accountable manner. This study will investigate the role of village heads as development administrators in Paccekke Village, Soppeng Riaja District, Barru Regency. This study employs qualitative descriptive research methods, utilizing data collection techniques such as observation, interviews, and documentation, which are then analyzed through reduction, presentation, and verification. The study uses planning, organizing, mobilizing, and supervision as its indicators. The results of the study show that the role of the village head as a development administrator in Paccekke Village, Soppeng Riaja District, Barru Regency, is included in the satisfactory level of implementation. The planning, organizing, mobilizing, and supervising processes clearly demonstrate this. The Paccekke village head's planning for village development is fairly effective, as demonstrated by the preparation of RPJMDes and RKPDes documents in a participatory manner that involves both village officials and community representatives in the development planning deliberations. The organizing carried out by the village head is fairly effective. The village head has divided the tasks among the village apparatus, and community involvement is carried out through deliberation and physical development activities. However, there are still obstacles related to the need to improve communication and expand citizen involvement so that development is more participatory and equitable. In terms of implementation, the village head demonstrates an effective managerial role. The village head actively provides direction and motivation to village officials and the community, as well as encourages their involvement in development. The supervisory function carried out by the village head is fairly effective; the village head conducts monitoring from the planning stage to evaluation and is equipped with routine reporting. The village head directly supervises the field and adjusts policies when technical obstacles arise. Overall, the Village Head's role as a development administrator in Paccekke Village is going well, although several aspects still need improvement.